DESTRUCTION OF MAJOR CARP FINGERLINGS IN A SECTION OF RIVER GANGA AND ITS PROBABLE ADVERSE EFFECTS ON FISH PRODUCTION - Jhingran, V G; Chakraborty, R D (Indian Journal of Fisheries, 2016)
Almost every year, towards the beginning of autumn when the floods commence to subside, the fingerlings of major carps form a sizeable riverine fishery in North India. This fishery is generally of a brief duration and often lasts for as short a time-span as 10 to 14 days, but it is extensive and is practised so intensely that for a few days the riverine catches consist almost exclusively of carp fingerlings. The types of areas fished comprise small creeks, rivulets, and fields inundated during the rains. The receding flood waters in autumn, in such habitats, leave the fingerUngs of carps stranded in shallows, rendering them an easy prey to fishermen, who capture them in great quantities.